Biological properties of Cu-bearing and Ag-bearing titanium-based alloys and their surface modifications: A review of antibacterial aspect - Ma, Yidan; Yan, Jiao; Yan, Tingting; Wang, Qiang; Bao, Zhifan; Yi, Zhe (Frontiers in Materials, 2022)
The use of titanium dental implants to replace missing teeth represents an important field of daily dental practice worldwide, which is highly reliable for long-term survival and success rates. However, titanium dental implants still have intrinsic problems that cannot meet the clinical requirements. Improving the performance of implants is an increasingly important area of dental research to reduce infection rates. Improved properties can be achieved by two main methods: 1) the overall change in the materials by changing the elemental composition and 2) surface modifications. This review provides an overview of various titanium-based alloys that have been employed to achieve a higher survival rate of implantation by adding elements or modifying the surface, with a special focus on their antibacterial applications. Recent developments in titanium-based alloys containing various antibacterial agents have been described in detail, including Cu-bearing, Ag-bearing, and Zr-bearing Ti alloys. Moreover, the applications of bioactive coatings and 3D printing materials with antibacterial properties are reviewed. This review aims to highlight the antibacterial challenges associated with titanium-based alloys to promote the further development and clinical application of antibacterial alloys.